PERILAKU SOSIAL PEKERJA SEKS KOMERSIAL (PSK) DI JALAN BAMBU KUNING KELURAHAN BAMBU KUNING KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Eka Linda Sari; Hambali Hambali; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to: (1) describe the social behavior of Commercial Sex Workers (PSK) in Jalan Bambu Kuning Bambu Kuning Sub-District Tenayan Raya Pekanbaru City, (2) describe the factors that cause women to be prostitutes in Jalan Bambu Kuning Kelurahan Bambu Yellow. This research is a case study research using qualitative approach. The subjects of the study were PSK, and Pimps as informants. Data collection used observation and in-depth interviews. Data analysis techniques used are display data, data reduction, and withdrawal conclusions. Result of research indicate: (1) social behavior of PSK in Jalan Bambu Kuning such as dressing according to requirement, and using perfume which smell very sting. PSK on Jalan Bambu Kuning operates day and night around Jondul Housing neighborhood, and salon. Salon is used by PSK to cover the actual profession. Social behavior is closely related to social interaction. Social interaction in this research include interaction of PSK with family, friends one profession, customer, and society in Jondul Street Bambu Kuning. Interaction begins with contact and communication, (2) the main factor that causes women to be prostitutes in Jalan Bambu Kuning is an economic factor. Being at the lower economic level makes PSK difficult to meet the economic needs.Keywords: Social Behavior, Commercial Sex Workers